Viability of Ischaemum rugosum Salisb. determined by the tetrazolium test - Portuguez-García, Mary Pamela (2021)
Introduction. The estimation of the viability of Ischaemum rugosum Salisb. with the tetrazolium test is a measure for the study of the weed’s biological dynamic. Objective. To evaluate the factors that affect the viability of I. rugosum Salisb using the tetrazolium test. Materials and methods. The work was carried out in the Laboratorio Oficial de Analisis de Calidad de Semillas del Centro para Investigaciones en Granos y Semillas of the Universidad de Costa Rica, San José, Costa Rica; in October 2015. I. rugosum Salisb. seeds were subjected to these treatments prior to the tetrazolium test: seed storage (room temperature: 23,9 °C and refrigerated temperature: 5 °C), imbibition (embedded and not embedded), caryopsid cut (with cut and without cut) and propagation unit (small caryopsis, large caryopsis, and spikelet). Seeds stained uniformly were counted as viable. Results. There was a significant interaction between storage temperature and propagation unit, the use of large caryopsis had a greater advantage over the small caryopsis (12.18 to 1) or the spikelet (181.27 to 1) and this result was stronger under room temperature. There was a significant interaction between propagation unit and cut, all the seeds required cutting so that tetrazolium could dye the tissues, the effect on the large seed was more conclusive than on the spikelet (1326.1 to 1) and that in the small one (7.39 to 1). The interaction of storage and imbibition temperatures and cutting and imbibition was significant. The seeds subjected to room temperature, embedded (41.26 to 1) and with cutting and imbibition (18.17 to 1) were more viable. Conclusion. The imbibition and cutting facilitated staining, the large seed and storage at room temperature influenced the viability of I. rugosum Salisb.